Self-Organized Complexity in the Physical, Biological, and Social Sciences (The National Academies Press, 2002)

In the Light of Evolution: Volume I: Adaptation and Complex Design - National Academy of Sciences
In December 2006, the National Academy of Sciences sponsored a colloquium (featured as part of the Arthur M. Sackler Colloquia series) on \

(NAS Colloquium) Proteolytic Processing and Physiological Regulation - National Academy of Sciences (The National Academies Press, 1999)

Promise and Challenges in Systems Microbiology: Workshop Summary - National Research Council (The National Academies Press, 2004)
Microbiologists have become interested in applying 201csystems biology201d to understand and harness complex biological processes in microbial communities. A systems approach, which attempts to use comparative, high-throughput assays, and mathematical or computational models, has been used to generate a picture of system-wide activity that can yield insight into processes operating within a single cell. But the concept of integrating advances in genomics, proteomics, and metabolomics and incorporating them into mathematical models can also be applied to microbial ecosystems, which typically occur in consortia of related and unrelated organisms. Research on microbial communities using a system-based approach could provide a broader perspective on controls on biological processes and how they operate in and among microorganisms. The National Academies of Sciences, Engineering, and Medicine held a workshop on 201cProgress and Promises of Systems Microbiology201d in August 2003, with the intent of providing a forum for discussion of the tools, technology, and programs that are needed to advance the study of microorganisms through a systems approach. Participants also discussed ways to encourage collaboration among scientists of different disciplines. This report summarizes the presentations and discussions from the workshop.

Recent Developments in Vision Research - National Research Council (The National Academies Press, 1966)

A New Biology for the 21st Century - National Research Council
Now more than ever, biology has the potential to contribute practical solutions to many of the major challenges confronting the United States and the world. A New Biology for the 21st Century recommends that a \

Engaging Scientists to Prevent Harmful Exploitation of Advanced Data Analytics and Biological Data: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Artificial intelligence (AI), facial recognition, and other advanced computational and statistical techniques are accelerating advancements in the life sciences and many other fields. However, these technologies and the scientific developments they enable also hold the potential for unintended harm and malicious exploitation. To examine these issues and to discuss practices for anticipating and preventing the misuse of advanced data analytics and biological data in a global context, the National Academies of Sciences, Engineering, and Medicine convened two virtual workshops on November 15, 2022, and February 9, 2023. The workshops engaged scientists from the United States, South Asia, and Southeast Asia through a series of presentations and scenario-based exercises to explore emerging applications and areas of research, their potential benefits, and the ethical issues and security risks that arise when AI applications are used in conjunction with biological data. This publication highlights the presentations and discussions of the workshops.

Synthetic Biology: Building on Nature's Inspiration: Interdisciplinary Research Team Summaries (The National Academies Press, 2010)
Synthetic biology is an innovative and growing field that unites engineering and biology. It builds on the powerful research that came about as a result of a recombinant DNA technology and genome sequencing. By definition, synthetic biology is an interdisciplinary enterprise comprising biologists of many specialties, engineers, physicists, computer scientists and others. It promises a fundamentally deeper understanding of how living systems work and the capacity to recreate them for medicine, public health and the environment, including renewable energy. NAKFI Synthetic Biology: Building a Nation's Inspiration discusses new foundational technologies and tools required to make biology easier to engineer, considers ethical issues unique to synthetic biology, explores how synthetic biology can lead to an understanding of the principles underlying natural genetic circuits and debates how synthetic biology can be used to answer fundamental biological questions.

Report of the Committee on Proposal Evaluation for Allocation of Supercomputing Time for the Study of Molecular Dynamics: Fourth Round - National Research Council (The National Academies Press, 2013)
This letter report evaluates proposals for allocation of time to the non-commercial research community on Anton, a supercomputer specially designed and built by D.E. Shaw Research (DESRES) that allows for dramatically increased molecular dynamics simulations compared to other currently available resources. Over the past three years (October 1, 2010 00e220ac201c September 30, 2013), DESRES has made available to the non-commercial research community node-hours on an Anton system housed at the Pittsburgh Supercomputing Center (PSC), based on the advice of previous National Research Council committees convened in 2010, 2011, and 2012.

The Role of Theory in Advancing 21st-Century Biology: Catalyzing Transformative Research - National Research Council
Although its importance is not always recognized, theory is an integral part of all biological research. Biologists' theoretical and conceptual frameworks inform every step of their research, affecting what experiments they do, what techniques and technologies they develop and use, and how they interpret their data. By examining how theory can help biologists answer questions like \

Inspired by Biology: From Molecules to Materials to Machines - National Research Council (The National Academies Press, 2008)
Scientists have long desired to create synthetic systems that function with the precision and efficiency of biological systems. Using new techniques, researchers are now uncovering principles that could allow the creation of synthetic materials that can perform tasks as precise as biological systems. To assess the current work and future promise of the biology-materials science intersection, the Department of Energy and the National Science Foundation asked the NRC to identify the most compelling questions and opportunities at this interface, suggest strategies to address them, and consider connections with national priorities such as healthcare and economic growth. This book presents a discussion of principles governing biomaterial design, a description of advanced materials for selected functions such as energy and national security, an assessment of biomolecular materials research tools, and an examination of infrastructure and resources for bridging biological and materials science.

Size Limits of Very Small Microorganisms: Proceedings of a Workshop - National Research Council (The National Academies Press, 1999)
How small can a free-living organism be? On the surface, this question is straightforward-in principle, the smallest cells can be identified and measured. But understanding what factors determine this lower limit, and addressing the host of other questions that follow on from this knowledge, require a fundamental understanding of the chemistry and ecology of cellular life. The recent report of evidence for life in a martian meteorite and the prospect of searching for biological signatures in intelligently chosen samples from Mars and elsewhere bring a new immediacy to such questions. How do we recognize the morphological or chemical remnants of life in rocks deposited 4 billion years ago on another planet? Are the empirical limits on cell size identified by observation on Earth applicable to life wherever it may occur, or is minimum size a function of the particular chemistry of an individual planetary surface? These questions formed the focus of a workshop on the size limits of very small organisms, organized by the Steering .Group for the Workshop on Size Limits of Very Small Microorganisms and held on October 22 and 23, 1998. Eighteen invited panelists, representing fields ranging from cell biology and molecular genetics to paleontology and mineralogy, joined with an almost equal number of other participants in a wide-ranging exploration of minimum cell size and the challenge of interpreting micro- and nano-scale features of sedimentary rocks found on Earth or elsewhere in the solar system. This document contains the proceedings of that workshop. It includes position papers presented by the individual panelists, arranged by panel, along with a summary, for each of the four sessions, of extensive roundtable discussions that involved the panelists as well as other workshop participants.

Advancing Disease Modeling in Animal-Based Research in Support of Precision Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Precision medicine is focused on the individual and will require the rapid and accurate identification and prioritization of causative factors of disease. To move forward and accelerate the delivery of the anticipated benefits of precision medicine, developing predictable, reproducible, and reliable animal models will be essential. In order to explore the topic of animal-based research and its relevance to precision medicine, the National Academies of Sciences, Engineering, and Medicine convened a 2-day workshop on October 5 and 6, 2017. The workshop was designed to focus on the development, implementation, and interpretation of model organisms to advance and accelerate the field of precision medicine. Participants examined the extent to which next-generation animal models, designed using patient data and phenotyping platforms targeted to reveal and inform disease mechanisms, will be essential to the successful implementation of precision medicine. This publication summarizes the presentations and discussions from the workshop.

Next Steps for Functional Genomics: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
One of the holy grails in biology is the ability to predict functional characteristics from an organism's genetic sequence. Despite decades of research since the first sequencing of an organism in 1995, scientists still do not understand exactly how the information in genes is converted into an organism's phenotype, its physical characteristics. Functional genomics attempts to make use of the vast wealth of data from \

In the Light of Evolution: Volume VII: The Human Mental Machinery - National Academy of Sciences
Humans possess certain unique mental traits. Self-reflection, as well as ethic and aesthetic values, is among them, constituting an essential part of what we call the human condition. The human mental machinery led our species to have a self-awareness but, at the same time, a sense of justice, willing to punish unfair actions even if the consequences of such outrages harm our own interests. Also, we appreciate searching for novelties, listening to music, viewing beautiful pictures, or living in well-designed houses. But why is this so? What is the meaning of our tendency, among other particularities, to defend and share values, to evaluate the rectitude of our actions and the beauty of our surroundings? What brain mechanisms correlate with the human capacity to maintain inner speech, or to carry out judgments of value? To what extent are they different from other primates' equivalent behaviors? In the Light of Evolution Volume VII aims to survey what has been learned about the human \

Systematics and the Origin of Species: On Ernst Mayr's 100th Anniversary - National Academy of Sciences (The National Academies Press, 2005)
In December 2004, the National Academy of Sciences sponsored a colloquium on 201cSystematics and the Origin of Species201d to celebrate Ernst Mayr2019s 100th anniversary and to explore current knowledge concerning the origin of species. In 1942, Ernst Mayr, one of the twentieth century2019s greatest scientists, published Systematics and the Origin of Species, a seminal book of the modern theory of evolution, where he advanced the significance of population variation in the understanding of evolutionary process and the origin of new species. Mayr formulated the transition from Linnaeus2019s static species concept to the dynamic species concept of the modern theory of evolution and emphasized the species as a community of populations, the role of reproductive isolation, and the ecological interactions between species. In addition to a preceding essay by Edward O. Wilson, this book includes the 16 papers presented by distinguished evolutionists at the colloquium. The papers are organized into sections covering the origins of species barriers, the processes of species divergence, the nature of species, the meaning of 201cspecies,201d and genomic approaches for understanding diversity and speciation.

(NAS Colloquium) Genetics and the Origin of Species: From Darwin to Molecular Biology 60 Years After Dobzhansky (The National Academies Press, 1997)

Calculating the Secrets of Life: Contributions of the Mathematical Sciences to Molecular Biology - National Research Council
As researchers have pursued biology's secrets to the molecular level, mathematical and computer sciences have played an increasingly important role2014in genome mapping, population genetics, and even the controversial search for \

Safeguarding the Bioeconomy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Research and innovation in the life sciences is driving rapid growth in agriculture, biomedical science, information science and computing, energy, and other sectors of the U.S. economy. This economic activity, conceptually referred to as the bioeconomy, presents many opportunities to create jobs, improve the quality of life, and continue to drive economic growth. While the United States has been a leader in advancements in the biological sciences, other countries are also actively investing in and expanding their capabilities in this area. Maintaining competitiveness in the bioeconomy is key to maintaining the economic health and security of the United States and other nations. Safeguarding the Bioeconomy evaluates preexisting and potential approaches for assessing the value of the bioeconomy and identifies intangible assets not sufficiently captured or that are missing from U.S. assessments. This study considers strategies for safeguarding and sustaining the economic activity driven by research and innovation in the life sciences. It also presents ideas for horizon scanning mechanisms to identify new technologies, markets, and data sources that have the potential to drive future development of the bioeconomy.

The Unique U.S.-Russian Relationship in Biological Science and Biotechnology: Recent Experience and Future Directions - National Research Council (The National Academies Press, 2013)
In the fall of 2010, the U.S. National Academies (consisting of the National Academy of Sciences, the National Academy of Engineering, and the Institute of Medicine) and the Russian Academy of Sciences (in cooperation with the Russian Academy of Medical Sciences and the Russian Academy of Agricultural Sciences) initiated a joint study of U.S.-Russian bilateral engagement in the biological sciences and biotechnology (hereinafter collectively referred to as bioengagement). The U.S. Department of State and the Russian Academy of Sciences provided support for the study. The academies established a joint committee of 12 leading scientists from the two countries to assess bioengagement activities since 1996 and to provide recommendations as to collaborative efforts in the near future. The Unique U.S.-Russian Relationship in Biological Science and Biotechnology: Recent Experience and Future Directions summarizes the principal conclusions and recommendations of the study.